A Data Mining Methodology for Detecting Conspiracy Theories from Scientific Articles: The Covid-19 Case - Raúl Isea; Rafael Mayo-García (International Journal of Coronaviruses, 2023)
The goal is to do a text mining analysis of all scientific publications and find out what journal and what aspects are studying about the conspiracy theories of Covid-19. For this purpose, all publications available in the National Center for Biotechnology Information (NCBI) database were consulted as they were peer-reviewed papers. Of all these papers, only the abstracts of each one were studied using artificial intelligence techniques to determine, for example, whether the subject is of importance depending on the journals where it has been published, and above all, what possible relationships could be extracted from the information published in them. In addition, the
Keywords: Text Mining